2020
DOI: 10.1002/1878-0261.12622
|View full text |Cite
|
Sign up to set email alerts
|

The long non‐coding RNA DANCR regulates the inflammatory phenotype of breast cancer cells and promotes breast cancer progression via EZH2‐dependent suppression of SOCS3 transcription

Abstract: Long non‐coding RNA (lncRNA) is involved in the regulation of tumorigenesis and metastasis. In this study, we focused on the clinical relevance, biological effects, and molecular mechanisms of the lncRNA differentiation antagonizing non‐protein coding RNA (DANCR) in breast cancer. We compared the expression of DANCR between breast cancer and normal tissues, and between breast cancer cell lines and normal breast epithelial cells using quantitative real‐time PCR (qRT‐PCR) analysis. By knocking down and overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 49 publications
(56 reference statements)
2
31
1
Order By: Relevance
“…Notably, MALAT1 regulates Zeb1 expression through miRNA sponging in hepatocellular carcinoma [112]. While DANCR was found to play a role in EMT [93], our analysis of the breast cancer patient tumor data does not reflect that finding. In fact, Zeb1 and Zeb2 are negatively correlated with DANCR expression.…”
Section: Breast Csc-associated Lncrna Correlations With Csc Markers Acontrasting
confidence: 57%
See 1 more Smart Citation
“…Notably, MALAT1 regulates Zeb1 expression through miRNA sponging in hepatocellular carcinoma [112]. While DANCR was found to play a role in EMT [93], our analysis of the breast cancer patient tumor data does not reflect that finding. In fact, Zeb1 and Zeb2 are negatively correlated with DANCR expression.…”
Section: Breast Csc-associated Lncrna Correlations With Csc Markers Acontrasting
confidence: 57%
“…DANCR expression was correlated with TNM stages, histological grade and lymph node metastasis, and decreased survival in TNBC patients. DANCR knockdown in MDA-MB-231 and MDA-MB-468 cells reduced EMT, stemness, and inflammation [93]. Furthermore, in the normal breast epithelial cell line MCF10A, overexpression of DANCR led to acquisition of EMT, cancer stemness and inflammation properties in the normal cells [93].…”
Section: Dancrmentioning
confidence: 98%
“…Recently, it have been shown that lncRNAs are widely involved in various biological processes regulation, including cell cycle, cell differentiation and many other life activities [25,26]. It is found that lncRNA has a great influence on the occurrence and development of liver cancer, laryngeal cancer, lung cancer and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…62 DANCR may also participate in the enhancer of zeste homolog 2 (EHZ2)-mediated epigenetic repression of the suppressor of cytokine signaling 3 (SOCS3) in breast cancer cells. 63 Sha et al 64 proposed DANCR knockdown was associated with increased binding of EZH2 to the promoters of CD44 and ABCG2 (two triplenegative breast cancer stem cell markers), and the concomitant reduction of expression of these genes decreased cancer cell proliferation and invasion. Furthermore, nanoparticle-mediated RNAi of DANCR was shown to be an effective therapy for triple-negative breast cancer.…”
Section: Breast Cancermentioning
confidence: 99%